THE CORRELATION BETWEEN GRAMMAR MASTERY AND READING COMPREHENSION OF THE SECOND GRADE STUDENTS OF SMPN 12 PEKANBARU - Yulia Andini; Hadriana '; Syofia Delfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This correlational study is aimed to find out the correlation between grammar mastery and reading comprehension of the second grade students of SMPN 12 Pekanbaru. The sample was chosen by using cluster random sampling as many as 37 students. The instrument used in this study was the tests; grammar test and reading comprehension test. Grammar test is used to know the students’ grammar mastery while reading comprehension test is used to find out the students’ ability in understanding a text. The obtained data were assessed by using Product Moments formula and analyzed by using SPSS 21.0 for windows. Based on the data analysis, it shows that there is moderate, significant and positive correlation between grammar mastery and reading comprehension of the second grade students of SMPN 12 Pekanbaru. Therefore, it answered the research question that there is a correlation between grammar mastery and reading comprehension.Key Words: Correlation, grammar mastery, reading comprehension